2016
DOI: 10.1002/2015tc004055
|View full text |Cite
|
Sign up to set email alerts
|

Tectonic interaction between the Pamir and Tien Shan observed by GPS

Abstract: The complex tectonic interplay between the Central Asian Southwest Tien Shan and the north advancing Pamir as well as the role of the Pamir Frontal Thrust (PFT) separating these two orogens along the intervening Alai Valley is yet unclear. In this paper we present data of the newly installed Western Alai GPS profile (WAGP), capturing the deformation signal of both mountain ranges. The 20 km long WAGP records a maximum displacement rate of 9.3 ± 0.8 mm yr À1 . The lion's share of displacement (6.0 ± 0.8 mm yr À… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(76 citation statements)
references
References 28 publications
4
72
0
Order By: Relevance
“…Velocities do not rotate along the eastern margin of the Pamir; there, the Pamir and the Tarim basin appear to move northward together as suggested by Sobel et al [], Ischuk et al [], and Thompson et al []. Velocities change abruptly across the PFTS, indicating significant strain localization there (Figure b) [ Zubovich et al , , ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Velocities do not rotate along the eastern margin of the Pamir; there, the Pamir and the Tarim basin appear to move northward together as suggested by Sobel et al [], Ischuk et al [], and Thompson et al []. Velocities change abruptly across the PFTS, indicating significant strain localization there (Figure b) [ Zubovich et al , , ].…”
Section: Resultsmentioning
confidence: 99%
“…This agrees with Flesch et al [] and Ghosh et al [], who found that stresses associated with both GPE and boundary conditions explain deformation in the India‐Eurasia collision zone. Since the stress field boundary conditions indicate no east‐west tension, gravitational collapse accounts for all east‐west extension in the deformation field [ Burtman , ; Stübner et al , , ; Schurr et al , ; Zubovich et al , ; Rutte et al , , ]. India‐Eurasia convergence explains the north‐south compression that dominates the stress field boundary conditions, but it cannot explain the rotation of principal deviatoric stress axes near the PFTS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During this northward movement, the Pamir crust was intensely shortened, and the once connected Tajik and Tarim basins were separated (Figure a). GPS measurements show that the rate of crustal shortening across the Pamir Thrust System, the present deformation front between the Pamir and the Tian Shan, is around 10–15 mm/year (Ischuk et al, ; Zubovich et al, , ). Pamir crust also extrudes westward into the Tajik basin forming a foreland fold and thrust belt, which is restricted to the north by the transpressional Illiac Fault zone.…”
Section: Regional Settingmentioning
confidence: 99%
“…The region is seismically active producing magnitude >6 earthquakes approximately every 10 years. Over the last 50 years, those occurred mainly along the Pamir's northern perimeter, the Pamir thrust system, which accommodates 13–19 mm/yr of the India‐Asia convergence (Ischuk et al, ; Zubovich et al, , ). The Pamir interior is seismically less active, both in long‐term global earthquake catalogs (Storchak et al, ) and observed by a dense local seismic network (Schurr et al, ).…”
Section: Introductionmentioning
confidence: 99%